The MADS-Box Gene MdDAM1 Controls Growth Cessation and Bud Dormancy in Apple - Moser, Mirko; Asquini, Elisa; Miolli, Giulia Valentina; Weigl, Kathleen; Hanke, Magda-Viola; Flachowsky, Henryk; Si-Ammour, Azeddine (Frontiers in Plant Science, 2020)
Apple trees require a long exposure to chilling temperature during winter to acquire competency to flower and grow in the following spring. Climate change or adverse meteorological conditions can impair release of dormancy and delay bud break, hence jeopardizing fruit production and causing substantial economic losses. In order to characterize the molecular mechanisms controlling bud dormancy in apple we focused our work on the MADS-box transcription factor gene MdDAM1. We show that MdDAM1 silencing is required for the release of dormancy and bud break in spring. MdDAM1 transcript levels are drastically reduced in the low-chill varieties ‘Anna’ and ‘Dorsett Golden’ compared to ‘Golden Delicious’ corroborating its role as a key genetic factor controlling the release of bud dormancy in Malus species. The functional characterization of MdDAM1 using RNA silencing resulted in trees unable to cease growth in winter and that displayed an evergrowing, or evergreen, phenotype several years after transgenesis. These trees lost their capacity to enter in dormancy and produced leaves and shoots regardless of the season. A transcriptome study revealed that apple evergrowing lines are a genocopy of ‘Golden Delicious’ trees at the onset of the bud break with the significant gene repression of the related MADS-box gene MdDAM4 as a major feature. We provide the first functional evidence that MADS-box transcriptional factors are key regulators of bud dormancy in pome fruit trees and demonstrate that their silencing results in a defect of growth cessation in autumn. Our findings will help producing low-chill apple variants from the elite commercial cultivars that will withstand climate change.